iPad e tablet per l'indagine multispettrale di opere d'arte - Cosentino, Antonino (Archeomatica, 2013)
iPad and Android tablets will have an increasing role for the imaging diagnostics of works of art. Their limited hardware risorces can be overcome using a web-server for images streaming by tile-based method such as IIPImage. This system allows not to have limits in the resolution of the images which can be streamed to multiple devices for collaborative projects.